2021
DOI: 10.1002/chem.202101773
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Interlocked Chiral Self‐Templated [2]Catenanes from 2,6‐Bis(1,2,3‐triazol‐4‐yl)pyridine (btp) Ligands

Abstract: We report the efficient self‐templated formation of optically active 2,6‐bis(1,2,3‐triazol‐4‐yl)pyridine (btp) derived homocircuit [2]catenane enantiomers. This represents the first example of the enantiopure formation of chiral btp homocircuit [2]catenanes from starting materials consisting of a classical chiral element; X‐ray diffraction crystallography enabled the structural characterization of the [2]catenane. The self‐assembly reaction was monitored closely in solution facilitating the characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Previous btp ligands have been most commonly reported in the anti-anti conformation, but in the presence of a cation such as a metal ion or a proton, the triazoles can adopt the syn-syn conformation. 23,35,36 In this case, the RNH 3 + of one ligand molecule, and the triazole N14 and N31 nitrogen atoms of the adjacent ligand molecule, form a hydrogen bonding interaction with an NÁ Á ÁN distance of 2.998( 6) and 2.885(6) Å, respectively, which causes the triazoles to adopt the syn-syn conformation.…”
Section: Crystallographic Characterisation Of [Hmentioning
confidence: 99%
“…Previous btp ligands have been most commonly reported in the anti-anti conformation, but in the presence of a cation such as a metal ion or a proton, the triazoles can adopt the syn-syn conformation. 23,35,36 In this case, the RNH 3 + of one ligand molecule, and the triazole N14 and N31 nitrogen atoms of the adjacent ligand molecule, form a hydrogen bonding interaction with an NÁ Á ÁN distance of 2.998( 6) and 2.885(6) Å, respectively, which causes the triazoles to adopt the syn-syn conformation.…”
Section: Crystallographic Characterisation Of [Hmentioning
confidence: 99%
“…This was recently demonstrated by our research group where we exploited the self-templating features of both chiral as well as achiral olefin btp precursors to synthesise homocircuit [2]catenanes and pseudo-rotaxanes using ring closing metathesis (RCM) reactions. 20,21 We have also been interested in the use of btp complexes in the formation of responsive polymers, and demonstrated that such complexes can be incorporated into HEMA polymers. 22 However, since these complexes are doped non-covalently into the polymer hosts, they are prone to leaching from the material during solvent swelling processes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Byrne and Gunnlaugsson have also demonstrated that the 2,6-btp motif can self-recognise through C-H⋯N hydrogen bonding, and have used this recognition to template the formation of catenanes. [38][39][40] We initially targeted macrocycles 34,35 containing the 2,6-btp motif as a possible route to catenanes containing both metal and anion binding motifs with the hope that these would be suitable for both anion and metal binding, and potentially also ion pair recognition 41,42 (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Byrne and Gunnlaugsson have also demonstrated that the 2,6- btp motif can self-recognise through C–H⋯N hydrogen bonding, and have used this recognition to template the formation of catenanes. 38–40…”
Section: Introductionmentioning
confidence: 99%